Growth and nonlinear saturation of electromagnetic ion cyclotron waves in multi‐ion species magnetospheric plasma. Issue 6 (29th June 2017) - Ofman, L.; Denton, R. E.; Bortnik, J.; An, X.; Glocer, A.; Komar, C.
Abstract: The growth and saturation of electromagnetic ion cyclotron (EMIC) waves is essential to the magnetospheric dynamics. Determining and isolating the effects of multiple ion parameters such as temperatures, anisotropies, and relative abundances is important for quantifying these processes in the magnetospheric plasma. In order to study these process, we utilize a 2.5‐D hybrid model (where ions are modeled with the particle‐in‐cell (PIC) method, and electrons are modeled as background neutralizing fluid) to study the nonlinear electromagnetic wave‐particle interactions of hot H +, cold H +, cold He +, and cold or hot O + ions for a broad range of typical magnetospheric parameters. The excitation of EMIC waves is driven by the temperature anisotropy of hot H + in our model. As a result, we quantify the parametric dependence of the linear growth, the nonlinear saturation level of perpendicular magnetic fluctuations, and the temporal evolution of the ion temperature anisotropies. We establish the relation between key plasma parameters and the saturated EMIC wave power, using either power law fits or a nonlinear regression method. We construct the dispersion relation of the waves using the results of the model and investigate the energy content in the various branches of the dispersion ( k ∥ − ω space), showing that the different modes can generate wave power in different regions of k space. We find that large O + concentration reduces the growth and saturated amplitude of the waves; but the waves are less sensitive to the temperature of the O + in the temperature range relevant to the magnetosphere. Key Points: The growth and nonlinear saturation of EMIC waves in multi‐ion magnetospheric plasma are studied with a 2.5‐D hybrid code The dependence of the saturated power of the magnetic fluctuations due to EMIC waves is established for key plasma parameters The effects of concentration and temperature of O + on the growth of EMIC waves in multi‐ion magnetospheric plasma is established